Relative age and anaerobic characteristics of young soccer players - Sekulic, Z.; Kokanovic, N.; Markovic, S. (SportLogia, 2019)
The aim of this study was to examine the impact of the relative age on the power, speed and agility of young U13 and U14 players. The study was conducted on a sample of 60 young soccer players born in 2001 and 2002. Within both age groups, players are divided into two categories according to relative age, whether they were born in the first or second half of the year. Anthropometric measurements and measurements of motor abilities were made to assess explosive power, speed and agility using the tests: standing long jump, vertical jump, sprint at 30 meters with passing time at 10 meters, zig-zag running without a ball and Ajax test 5x10m. Statistically significant differences were found in body height and weight, as well as in tests to assess power in a sample of U13 players. In U14 group, differences were found in tests of power and running speed, while there were no statistically significant differences in anthropometric variables. According to the results obtained, it can be said that the relative age is an important factor that leads to the appearance of differences in the test results of motor skills of young U13 and U14 soccer players. Therefore, the effect of relative age must be taken into account when selecting young soccer players during adolescence.